Beyond South Africa's 'indigenous knowledge - science' wars - Lesley Green (South African Journal of Science)
In this paper, the paradoxes and difficulties attending the notion of indigenous knowledge in South Africa are reviewed and an alternative dialogue about intellectual heritage is proposed. Beginning with a survey of debates on 'indigenous knowledge' and sciences in India, Australia and Latin America, the discussion draws attention to differences in regional discussions on the subject of knowledge diversity. Turning to the South African context, the paper foregrounds contradictions in the debate on traditional medicines and the sciences in relation to HIV. The bifurcation of 'indigenous knowledge' and 'science' is argued against. Debates on both indigenous knowledge and science within the critical humanities in South Africa have been characterised by denunciation: an approach which does not facilitate the important discussions needed on intellectual heritage, or on the relationship between sciences and coloniality. In dialogue with current research on the anthropology of knowledge, strategies are proposed to broaden the possibilities for scholarship on knowledge, sciences, and different ways of understanding the world.